From diversity to talents: the perspective of primary school children - Coin, Francesca (Formazione & insegnamento, 2018)
Over the years, the definition of talent has changed strongly: from one-dimensional, additive and static to multidimensional, multiplicative and dynamic. Consequently, the educator’s task changes: not to design individualized learning paths, but to create settings that allow everyone to have productive interactions between themselves and the environment. However, only during adolescence do the skills necessary to reflect on one’s own abilities, objectives, demands and possibilities offered by the context mature and allow one to combine them and transform talent from potential to success, to make it available to the community. The knowledge of the stages of children’s development, of how they interpret diversity and the possibilities of using it for complex aims, is essential to adequately support even younger children. Through a nursery rhyme, the theme of diversity was introduced to some primary school classes. Eighty-four children marked their conception of diversity through drawings. The sketches were then analysed to understand the stages and trajectories that their reflections run through during development.